Model integrasi penentuan lokasi pusat distribusi pada jaringan hub and spoke: studi kasus pusat distribusi di Jawa Timur - Fitri Agustina; Nachnul Ansori; Trisita Novianti; Ernaning Widiaswanti (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
Strategic planning for the supply chain is part of the planning process for the supply chain management. One part of this process is figuring out the supply chain's infrastructure and physical structure. The design of supply chain networks has been used for facility location models for more than 20 years. The hub and spoke system is a two-level distribution network with a hub that handles shipments and spokes that connect with consumers. This study integrates optimization techniques with decision-making tools to determine the best location for distribution centers. The optimization method is modified by considering population, income, and distance factors. The location of the distribution center is determined at two levels. The first level uses the set covering method, while the second uses the Analytical Hierarchy Process (AHP). A case study is drawn from this research: a company that will determine regional and local distribution centers in East Java. The result is four regional distribution centers: Pacitan, Kediri, Banyuwangi, and Sumenep. Each regional distribution center has two local distribution centers: Pacitan (Tulungagung and Madiun), Kediri (Bojonegoro and Jombang), Banyuwangi (Pasuruan and Malang), and Sumenep (Surabaya and Gresik). This study illustrates how the integration of two-level method can be applied in the context of strategic decision making. The selected locations have a minimum total cost and can serve consumers with maximum coverage in the region. Finally, an efficient supply chain network with a high service level will be obtained.